Study of job satisfaction and its relationship with organizational citizenship behaviour (ocb) in Sibu divisional administration office / Grace Telon Joseph - Joseph, Grace Telon (2015)
The purpose of this study is to examine the relationship between job satisfaction and organizational citizenship behaviour (OCB) among the employees in Sibu Divisional Administration Office. The sample data are derived from a questionnaire survey of 102 employees in Sibu Divisional Administration Office. The survey was conducted to investigate the job satisfaction and their organizational citizenship behaviour (OCB) using a 5-point Likert- scale research instrument that was developed based on the work of Smith, Kendall and Hulin (1996) and that of Podsakoff and MacKenzie (1994). Based on the analysis, it is found that overall; job satisfaction has significant relationship to OCB.